Babachahi and Linguistic Components of Postmodern Poetry - Mohammadamin Ehsani Estahbanati; Mohammad reza Sarfi (مطالعات زبانی و بلاغی)
Postmodernism is a powerful cultural, political, and literary movement emerging since the 1970s. The history of human thought can be divided into three periods: premodern, modern, and postmodern. The third period, starting from the late 19th Century to the present time, replaces the discovery of reality with the creation of reality; during such a period, human contribution in knowledge construction becomes more predominant. This powerful movement is mainly based on theories provided by poststructuralists. Some components of postmodern poetry are as follows: in postmodern poetry, meaning is avoided and any type of meaning domination or strange narrative, based on strength of the poet in terms of meaning, is denied; belief in certainty and seriousness as features of art and poetry of the modern period do not exist in the postmodern artistic and literary school of thought; Form, structure, and meaning would be disarranged through schizophrenic images governing the poem, and its linear structure would be overshadowed. According to its founders, this type of poetry is rooted in the political, cultural, and social conditions of humans in the current era. One of the pioneering representatives of postmodernism in Iran is Ali Babachahi. His literary works are the best and most distinctive samples for explaining postmodernism and its language in Persian literature. The results of this article have been obtained through descriptive-analytical research and are based on document mining and library studies, as well as an inductive method based on the findings of authors. The following components would be dealt with in Babachahi poems: avoiding syntax; distracted language structure, the emphasis put on bypassing the wisdom, lack of integration and certainty, etc.